2022
DOI: 10.21037/tcr-22-264
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and significance of T lymphocyte subsets in peripheral blood of osteosarcoma mice

et al.

Abstract: Background Osteosarcoma (OS) is the most common malignant bone tumor, which often has lung metastasis. The survival rate after tumor metastasis is very low. Treatments including the antitumor immunocompetence of innate immune cells are found favorable for OS tumor. However, as a major means of early tumor detection, there are still few studies on T cells in peripheral blood of OS patients. Methods OS cells were implanted into the femoral bone marrow cavity of C3H/HeN mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previous studies confirmed that Treg cells are involved in the tumor development process by suppressing antitumor immunity and its high expression level represents a poor prognosis ( 45 ). γδ T cells, a congenital cytotoxic T cells, were highly infiltrated in the low-risk group, which may be related to the fact that osteosarcoma is an immunocompromised tumor ( 46 ). Moreover, LAIR1, HAVCR2, CD27, CTLA4, CD48, CD44, LAG3 and LGALS9 were highly expressed in the low-risk group, indicating that the low-risk group was more likely to benefit from more types of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that Treg cells are involved in the tumor development process by suppressing antitumor immunity and its high expression level represents a poor prognosis ( 45 ). γδ T cells, a congenital cytotoxic T cells, were highly infiltrated in the low-risk group, which may be related to the fact that osteosarcoma is an immunocompromised tumor ( 46 ). Moreover, LAIR1, HAVCR2, CD27, CTLA4, CD48, CD44, LAG3 and LGALS9 were highly expressed in the low-risk group, indicating that the low-risk group was more likely to benefit from more types of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as an important means of clinical research. [ 20 , 21 ] Decreased CD4+/CD8+ ratio is an important indication of immunodeficiency disease. In patients with acquired immunodeficiency syndrome, there is a significant reduction in the number of CD4+ cells, so the CD4+/CD8+ ratio is often inverted.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of T-cell dysfunction in these disorders involves an imbalance in the expression of certain immune-related genes. For example, studies have shown that the expression of FOXP3, a gene involved in the function of regulatory T-cells, is reduced in patients with T-cell disorders [ 31 ]. Thymus-derived regulatory T-cells (Tregs) play a crucial role in immune regulation by suppressing the activation of other T-cell subsets, such as Th17 and Th1 cells [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…For example, studies have shown that the expression of FOXP3, a gene involved in the function of regulatory T-cells, is reduced in patients with T-cell disorders [ 31 ]. Thymus-derived regulatory T-cells (Tregs) play a crucial role in immune regulation by suppressing the activation of other T-cell subsets, such as Th17 and Th1 cells [ 31 ]. This impairment of Treg-mediated immunosuppression, coupled with the increased expression of genes associated with Th17 and Th1 cells, suggests a dysregulation of the immune response in individuals with T-cell disorders [ 31 ].…”
Section: Reviewmentioning
confidence: 99%